The Impact of Institutions on Innovation - Alexander Donges; Jean-Marie A. Meier; Rui C. Silva (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper studies the impact of radical institutional reform on innovation. We use the timing and geography of French invasions of different regions of Germany after the French revolution of 1789 as an exogenous shock to the institutions of those regions. German regions that were invaded by the French subsequently changed their institutions in important ways, including the introduction of the civil code, the dissolution of guilds, the abolition of serfdom and the implementation of agrarian reforms. These institutional changes in turn affect innovation. Using patents per capita as our measure of innovation, we show that counties whose institutions are more inclusive as a result of the French occupation also become more innovative. Moving from a county with no occupation to a county with the longest occupation, the implied changes in institutional reforms result in an increase of patents per capita of 123%. Our findings point to institutions as a first order determinant of innovation and highlight the role of innovation as a key mechanism through which institutions may foster economic growth.
Keywords: N13; O31; O33; 330